Formulasi Sediaan Blush Cream dari Ekstrak Biji Kesumba Keling (Bixa orellana (L.)) sebagai Pewarna Alami Kosmetik - Nova Mega Handayani; Lisna Meylina; Angga Cipta Narsa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Blush is a type of decorative cosmetics used in the cheek area there used with the aim of adding aesthetic value to the face so that the face looks prettier, fresher and has more dimension. Currently there are many blush preparations on the market that contain hazardous chemicals, then a blush preparation made from kesumba keling seed extract containing bixin as natural coloring is made. The purpose of this study was to formulation and evaluate blush cream preparations by utilizing the acetone and maceration is concentrated with a rotary vacuum evaporator. Blush cream formula made using dyes from kesumba keling seed extract with a concentration of 0.5%, 1%, 2%, and 3% into the chosen base formula that produced color in successive orange-yellowish, soft-orange, dark-orange and orange-brownish color. Evaluations undertaken include organoleptic, homogeneity test, dispersion test, pH test, viscosity test and preferences test. The results obtained are based on parameters test, namely the four formulas enter the required value range. Aseptability test results showed that the preparation of blush cream with a concentration of 2% of the most preferred color of kesumba rivet seed extract and at a concentration of 0.5% was the easiest to spread.